2017
DOI: 10.1186/s13046-016-0478-9
|View full text |Cite
|
Sign up to set email alerts
|

FGF19/FGFR4 signaling contributes to the resistance of hepatocellular carcinoma to sorafenib

Abstract: BackgroundSorafenib, a multi-kinase inhibitor, is used as a standard therapy for advanced hepatocellular carcinoma (HCC). However, complete remission has not been achieved and the molecular basis of HCC resistance to sorafenib remains largely unknown. Previous studies have shown that fibroblast growth factor 19 (FGF19) expression correlates with tumor progression and poor prognosis of HCC. Here, we demonstrate the novel role of FGF19 in HCC resistance to sorafenib therapy.MethodsFGF19 Knockdown cells were achi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
101
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(102 citation statements)
references
References 40 publications
1
101
0
Order By: Relevance
“…Up-regulation of FGFR4 is associated with multiple oncogenic functions in cancer, including cell survival, proliferation, apoptosis, migration, and chemoresistance [14, 18]. A role for FGFR4 in chemoresistance has recently been described for hepatocellular carcinoma and colorectal cancer [35, 36]. Here, using a loss-of-function study, we showed that FGFR4 knockdown improves the chemotherapy response of ADR-R cells to ADR treatment and suppresses glycolytic flux.…”
Section: Discussionmentioning
confidence: 87%
“…Up-regulation of FGFR4 is associated with multiple oncogenic functions in cancer, including cell survival, proliferation, apoptosis, migration, and chemoresistance [14, 18]. A role for FGFR4 in chemoresistance has recently been described for hepatocellular carcinoma and colorectal cancer [35, 36]. Here, using a loss-of-function study, we showed that FGFR4 knockdown improves the chemotherapy response of ADR-R cells to ADR treatment and suppresses glycolytic flux.…”
Section: Discussionmentioning
confidence: 87%
“…A recent clinical report showed that FGF19 expression is associated with cancer progression and poor prognosis in HCC . Other preclinical studies have demonstrated that FGF19 may serve as a predictive biomarker for primary resistance to sorafenib in HCC, as FGF19 silencing in sorafenib‐resistant cells significantly increased the sensitivity to sorafenib . In breast cancer, neutralization of extracellular FGF19 by anti‐FGF19 antibody or siRNA‐mediated knockdown of FGF19 can decrease the p‐AKT level, suppress cancer cell growth, and enhance doxorubicin sensitivity …”
Section: Discussionmentioning
confidence: 99%
“…The interaction of ligand and receptor mediates almost all related biological activities at both the N and C terminals of FGF19. A previous study suggested that the FGF19‐FGFR4 signaling axis may be a crucial player, contributing to the development of a certain type of hepatocellular carcinoma (HCC), drawing great attention to therapeutic intervention of the FGF19/FGFR4 autocrine loop in this disease setting . Small interfering RNA (siRNA)‐mediated silencing of FGF19 was also reported to decrease AKT phosphorylation, inhibit cancer cell growth, and sensitize doxorubicin treatment in both FGFR4 and FGF19 positive breast cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…Gao et al found that FGF19 is essential for sorafenib efficacy and resistance in the treatment of HCC 61. The authors have demonstrated that elevated FGF19 expression or hyperactivation of FGF19/FGFR4 signaling in HCC cells is one of the main mechanisms of sorafenib resistance 61.…”
Section: Drug Resistancementioning
confidence: 99%